Impact Assessment of NEP and IPR on Institutes of Higher Education (Journal of Intellectual Property Rights (JIPR), 2024)
Youth nowadays can be considered as a wonderful reservoir of potential and innovation which is mostly untapped. Theirnew perspectives, vigour, curiosity, professionalism, and aspiration for a secured and better future are alreadyrevolutionising methods and igniting initiatives for innovation and change. Today’s youth is demonstrating the ability tomobilise and spark support for change because they grew up in the internet era. Many people are devoting their energy aswell as time in creating cutting-edge technologies and novelties to address the major problems of recent time, such as globalwarming, education, food security, access to healthcare, unemployment, and other issues. The youth can, however,overcome the challenge of creating a viable firm by knowing how to look after their intellectual property (IP) assets.(i.e., their creations and discoveries), harnessing their value, and increasing influence. The National Education Policy (NEP)2020 focuses on the educational sector's vision for a contemporary India and aspires to meet the quality education target outlined in the United Nations Sustainable Development Goals for Education by 2030. Major changes to higher education have been made as a result of the NEP 2020, which are in line with the need to offer "inclusive and equitable quality education and promoting lifelong learning opportunities for all" (SDG 4), crucial to manage the demands of employment and bringing about a collective systemic change. It is crucial that the next generation understand how integral intellectual property is to their vision as they get ready to enter the workforce. In this regard, this paper examines how NEP affects higher education institutions (HEIs), how IPR fits into NEP, and how the New Education Policy and IPR policy together might cause a paradigmatic change in the current higher education system.